Endoscopic dacryocystorhinostomy and obstructive sleep apnoea: the effects and outcomes of continuous positive airway pressure therapy. (15th January 2015) - Ali, Mohammad J; Psaltis, Alkis J; Murphy, Jae; Wormald, Peter John
Abstract Background This study aims to assess the effects and outcomes of continuous positive airway pressure (CPAP) therapy for obstructive sleep apnoea (OSA) in patients who have undergone endoscopic dacryocystorhinostomy (DCR). Design Retrospective series in a university setting. Participants A total of 205 consecutive patients were included in this study. Methods A 10‐year retrospective review was performed of 205 consecutive patients who had undergone powered endoscopic DCR for nasolacrimal duct obstruction. Patient notes were reviewed for demographic, clinical and surgical information. In addition, all patients were contacted and asked to complete a standardized telephone survey relating to OSA, CPAP use and associated symptoms. Main Outcome Measure Effects of CPAP following DCR. Results Ten of the 205 patients undergoing DCR were identified to use CPAP for obstructive sleep apnoea. Eight patients were initiated on a nasal device, while two used a full‐face mask. The mean CPAP pressures were 8 cm H20 (range: 6–10 cm H20). Eighty per cent (8/10) of patients complained of symptoms from the use of their CPAP following DCR. The most commonly described symptom was that of air regurgitation in 70% of patients followed by ophthalmic symptoms in 60% (6/10). 50% (5/10) of patients discontinued their CPAP as a consequence of their symptoms with 20% (2/10) discontinuing because of intolerable ophthalmic symptoms. Conclusion Symptoms from CPAP use post‐endoscopic DCR are a common occurrence and may contribute to poor compliance with CPAP therapy. Detailed preoperative counseling with regards to CPAP use and its effects should be mandatory in known or at risk OSA patients undergoing DCR.